The Freemason Simón Bolívar between myth and historical truth - Benimeli, José Antonio Ferrer (2020)
The figure of Simón Bolívar in relation to Freemasonry, as well as the rest of the heroes of Spanish American independence, remains controversial despite recent research to clarify the issue. It is therefore a matter of updating historical knowledge -neither Masonic nor anti-Masonic- about this relationship through the latest studies.